Double feedback control-based H∞ admissibilization for hybrid descriptor systems subject to external impulses and fast varying delays - Zhuang, Guangming; Xu, Shengyuan; Xia, Jianwei; Ma, Qian (Systems & control letters, 2024)
This paper is concerned with the H∞ admissibilization for hybrid descriptor systems subject to external impulses, Markovian jumping and fast varying delays characteristics by virtue of designing double feedback controllers. The neoteric double feedback controllers are composed of normal state feedback controller and impulsive controller, not only the internal impulses can be eliminated, but also the external destabilizing impulses can be overcome and state jumps at switching instants can be suppressed. Impulse time dependent, delays dependent and Markovian jump modes dependent Lyapunov–Krasovskii functional is developed, and the improved free-weight matrix technique is employed to effectively capture the hybrid characteristics and realize the innovative conditions of H∞ admissibilization for descriptor impulsive Markovian jump systems with fast varying delays. By utilizing M-P matrix inversion approach and matrix transformation technology, the desired double feedback controllers gains are acquired in terms of linear matrix inequalities. RLC electrical circuit system is applied to demonstrate the availability and practicability of the addressed designing schemes.